2003
DOI: 10.1074/jbc.m210756200
|View full text |Cite
|
Sign up to set email alerts
|

BcR-induced Apoptosis Involves Differential Regulation of C16 and C24-Ceramide Formation and Sphingolipid-dependent Activation of the Proteasome

Abstract: In this study, we describe an ordered formation of long-and very long-chain ceramide species in relation to the progression of B-cell receptor (BcR) triggering induced apoptosis. An early and caspase-independent increase in long-chain ceramide species, in which C 16 -ceramide predominated, was observed 6 h after BcR triggering. In contrast, very long-chain ceramide species were generated later, 12-24 h after BcR triggering. The formation of these very long-chain ceramide species, in which C 24 -ceramide predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 52 publications
4
78
0
Order By: Relevance
“…Similarly, C24-ceramide has been associated with apoptosis [26]. The biological significance of specific fatty acyl chains in ceramides remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, C24-ceramide has been associated with apoptosis [26]. The biological significance of specific fatty acyl chains in ceramides remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have shown that de novo generated ceramide in response to stimulation of the BcR receptor in B cells results in selective accumulation of C 16 -ceramide (23), and this was implicated in the apoptotic response of those cells (24). On the other hand, activation of neutral SMase2 was shown to selectively induce the formation of C 24 -ceramide and C 24:1 -ceramide, and evidence was provided for a role for this pathway in cell cycle regulation (25) and in interleukin-6 formation (26).…”
Section: Discussionmentioning
confidence: 99%
“…We characterized UV-C-induced ceramide generation in WT BMK cells (Fig. 1c) and found that total ceramide was elevated as early as 2 h following irradiation and continued to increase up to 24 h. Because ceramides with specific chain lengths have been shown to contribute differently to cellular responses to stress stimuli (24,25), we determined the specific ceramides elevated following UV-C irradiation. In WT cells, UV-C irradiation increased most significantly the long-chain ceramides (C 16 , C 18 , and C 20 ; Fig.…”
Section: Bak/bax and Ceramide Generation Are Necessary For Uv-cmentioning
confidence: 99%